High-thermal-conductivity magnesium alloy sheet and preparation method thereof

Through the preparation method of Mg-Zn-Y-Ca alloy, the problems of difficulty in forming and insufficient thermal conductivity of magnesium alloy thin plates are solved, and high thermal conductivity and excellent molding ability are achieved, which is suitable for the application of electronic devices and heat dissipation structures.

CN119121018APending Publication Date: 2024-12-13SHANGHAI JIAOTONG UNIV

Patent Information

Application Number
CN202411243075.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing commercial magnesium alloy thin plate molding is difficult and the thermal conductivity is insufficient, which limits its application in the field of lightweight heat dissipation materials.

Method used

Using Mg-Zn-Y-Ca alloy, a high-thermal magnesium alloy thin plate was prepared by heating and melting raw materials, homogenizing heat treatment, hot extrusion and multi-pass hot rolling processes. The magnesium alloy was improved by reasonable elemental composition and process design. molding ability and thermal conductivity.

Benefits of technology

It has achieved smooth forming and high thermal conductivity of magnesium alloy thin plates, with excellent mechanical properties and commercial application prospects, with relatively simple process and low cost, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121018A_ABST
    Figure CN119121018A_ABST
Patent Text Reader

Abstract

The invention relates to a high-thermal-conductivity magnesium alloy sheet and a preparation method thereof. The alloy sheet consists of the following elements in percentage by weight: 1.0-5.0% of Zn, 0-0.8% of Y, 0-0.7% of Ca, 0.1-0.5% of Mn and the balance of Mg and inevitable impurity components. The invention aims to solve the problems that a commercial magnesium alloy sheet is difficult to form and the heat-conducting property is insufficient, and is based on the component design of magnesium alloy and the cooperation of heat treatment and thermal deformation processes; the adopted raw materials are relatively low in cost, the process is relatively simple, the large-size magnesium alloy sheet can be prepared, and further industrial production and application of magnesium alloy are facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of magnesium alloys and relates to a high thermal conductivity magnesium alloy sheet and a preparation method thereof. Background Art

[0002] As electronic devices continue to develop towards miniaturization, integration, lightweight and high performance, huge heat dissipation needs have been generated in the fields of mobile electronic products and electric vehicles. As the lightest metal structural materials, magnesium and magnesium alloys also have excellent thermal conductivity. In addition, the excellent weight reduction, endurance and recycling characteristics of magnesium and magnesium alloys are expected to make important contributions in energy conservation, emission reduction and carbon balance. However, the thermal conductivity of commercial magnesium alloys currently in widespread use is relatively limited, which greatly limits the application of magnesium alloys in the field of lightweight heat dissipation materials. On the other hand, the formability of magnesium alloys is also worthy of attention: limited by the poor coordinated deformation ability of magnesium's own close-packed hexagonal structure, the preparation of magnesium alloy sheets still faces many difficulties. In short, high thermal conductivity magnesium alloy sheets have great potential application prospects in the fields of electronic device housings and heat dissipation structures, and the key to their technology lies in the excellent thermal conductivity and forming ability of magnesium alloys.

[0003] Chinese patent CN202110790189.9 discloses a method for preparing a high-strength and high-thermal-conductivity magnesium alloy, which is a Mg-Zn-Ca ternary alloy. The specific preparation process is: first, raw materials such as pure magnesium ingots, pure zinc particles, and magnesium-calcium master alloys are cast into magnesium alloy ingots; then, cutting, homogenization heat treatment, and quenching are performed in sequence to obtain homogenized ingots; then, preheating, isothermal extrusion, and quenching are continued to obtain extruded bars. This patent achieves high strength by introducing a large amount of Ca elements in conjunction with a hot extrusion process to achieve grain refinement of the magnesium alloy, but due to composition and process factors, it cannot achieve thin plate forming. Summary of the invention

[0004] The purpose of the present invention is to provide a high thermal conductivity magnesium alloy sheet and a preparation method thereof, so as to solve the problems that the existing commercial magnesium alloy sheets are difficult to form and have insufficient thermal conductivity.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] One of the technical solutions of the present invention provides a high thermal conductivity magnesium alloy sheet, which is composed of the following elements in weight percentage: Zn 1.0% to 5.0%, Y 0% to 0.8%, Ca 0% to 0.7%, Mn 0.1% to 0.5%, and the rest is Mg and inevitable impurities.

[0007] Furthermore, the content of Y is not 0, and can be specifically 0.1 to 0.8%.

[0008] Furthermore, the content of Ca is not 0. Specifically, it can be 0.2 to 0.5%.

[0009] Furthermore, the content of Zn is 3%, the content of Y is 0.2%, the content of Ca is 0.5%, and the content of Mn is 0.2%.

[0010] A second technical solution of the present invention provides a method for preparing a high thermal conductivity magnesium alloy sheet, comprising the following steps:

[0011] (1) heating and melting raw materials providing Zn, Y, Ca, Mn and Mg to obtain a mixed solution, keeping the solution at the temperature and allowing it to stand, cooling the solution to remove the slag and oxide layer on the surface, and then casting the solution to obtain a magnesium alloy ingot;

[0012] (2) subjecting the obtained magnesium alloy ingot to homogenization heat treatment, and then quenching to obtain a homogenized ingot;

[0013] (3) preheating the homogenized ingot and then isothermally extruding it to obtain a magnesium alloy sheet;

[0014] (4) The magnesium alloy sheet is hot rolled and annealed to obtain a magnesium alloy thin plate, which is the product.

[0015] Furthermore, the raw materials for providing Zn, Y, Ca, Mn and Mg include pure magnesium, magnesium-calcium master alloy, pure zinc particles, magnesium-yttrium master alloy and magnesium-manganese master alloy.

[0016] Furthermore, in step (1), during the preparation of the magnesium alloy ingot, a flowing mixed gas is introduced for anti-oxidation protection, wherein the mixed gas consists of 99 vol. % CO2 and 1 vol. % SF6.

[0017] Furthermore, in step (1), during the smelting and preparation of the magnesium alloy ingot, a layer of covering agent, refining agent, etc. can be sprinkled on the surface of the magnesium melt to protect the magnesium melt from oxidation. Specifically, the covering agent can be selected as RJ-2, and the amount used each time can be 1% to 2% of the mass of the magnesium melt. During the smelting process, the covering agent can be sprinkled once as needed when adding alloying elements, slag removal and refining to the magnesium melt. The refining agent is composed of covering agent RJ-2 and CaF2, and the mass ratio of covering agent RJ-2 to CaF2 is 19:1; the amount of refining agent added is 8 grams of refining agent per kilogram of alloy. It should be pointed out here that the covering agent and refining agent can be added together during the smelting process, or only one can be added. This part belongs to the existing conventional technology and does not belong to the innovative protection point of the present invention.

[0018] Furthermore, in step (2), the process conditions for the homogenization heat treatment are: first heat treatment at 320°C for 6 hours, then heat treatment at 430°C for 14 hours, and finally heating to 520°C for 4 hours.

[0019] Furthermore, in step (2), the homogenization heat treatment is carried out in a vacuum heat treatment furnace under a pure argon protective atmosphere.

[0020] Furthermore, in step (3), the preheating temperature is 250°C to 400°C.

[0021] Furthermore, in step (3), the process conditions of isothermal extrusion are: extrusion ratio of 10 to 25:1, extrusion speed of 0.01 mm·s -1 ~25mm·s -1 , the extrusion temperature is 200℃~350℃.

[0022] Furthermore, the magnesium alloy sheet obtained by the extrusion process has a thickness of 2.5 mm to 10 mm and a width of 50 mm to 250 mm.

[0023] Furthermore, in step (4), the magnesium alloy is subjected to multiple hot rolling passes, wherein the reduction in the first rolling pass (based on the workpiece before the current rolling pass) is controlled at 5% to 10%, the reduction in the intermediate passes is controlled at 10% to 30%, and the reduction in the final rolling pass is controlled at 10% to 40%.

[0024] Furthermore, in step (4), before each rolling, the magnesium alloy sheet is kept at 300-350°C, and the holding time varies with the thickness of the sheet. When the thickness of the magnesium alloy sheet is 5-10 mm, the holding time is 30 min; when the thickness of the magnesium alloy sheet is 2-5 mm (excluding 5 mm), the holding time is 20 min; when the thickness of the magnesium alloy sheet is less than 2 mm, the holding time is 10 min. Preferably, the holding temperature is 320°C.

[0025] Furthermore, in step (4), the annealing temperature is 200° C. to 350° C., and the annealing time is 10 min to 2 h.

[0026] During the material preparation process, a reasonable homogenization heat treatment temperature can effectively remove the element segregation inside the ingot and eliminate the element segregation at the dendrite interface. If the heat treatment temperature is too high, it will cause overburning; if the heat treatment temperature is too low, the segregation effect cannot be completely eliminated, which is not conducive to the subsequent hot deformation process. In addition, a reasonable rolling process design is conducive to the smooth forming of magnesium alloy sheets. The reasonable selection of alloying elements is not only conducive to improving the plastic deformation ability of magnesium alloys, but also an important guarantee for their high thermal conductivity.

[0027] The atomic size of the alloying element Zn added by the present invention is close to that of Mg and the valence of its ions is consistent with that of Mg, so it has little effect on the thermal conductivity of the magnesium alloy. At the same time, Mn is introduced to remove impurities, reduce the content of Fe, Cu, Ni and other elements harmful to the alloy, and purify the alloy melt. In addition, adding a trace amount of Y element weakens the texture and promotes the non-basal slip, thereby enhancing the forming ability of the magnesium alloy. At the same time, due to the high price of Y element, its excessive addition not only greatly increases the economic cost, but also affects the thermal conductivity of the alloy material.

[0028] The solid solubility of Ca in magnesium is extremely low, which is beneficial to the thermal conductivity of magnesium alloys. In addition, the presence of Ca can refine the matrix grains and improve the strength of magnesium alloys. The Mg-Zn-Y-Ca alloy proposed in the present invention has excellent forming ability after relatively simple smelting, homogenization treatment, and hot extrusion, and the rolled plate thickness can reach less than 1 mm. The comprehensive mechanical and thermal conductivity of the Mg-Zn-Y-Ca alloy sheet proposed in the present invention is very excellent, and has great commercial application prospects.

[0029] Compared with the prior art, the method for preparing the high thermal conductivity magnesium alloy sheet proposed in the present invention is based on the composition design of the magnesium alloy and the coordinated cooperation of the heat treatment and thermal deformation processes. The raw materials used are relatively cheap, the process is relatively simple, and large-sized magnesium alloy sheets can be prepared, which is conducive to the further industrial production and application of magnesium alloys. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is the macroscopic morphology of the Mg-3Zn-0.2Y-0.5Ca-0.2Mn alloy extruded plate in Example 2 of the present invention.

[0031] Figure 2 This is the macroscopic morphology of the Mg-3Zn-0.2Y-0.5Ca-0.2Mn alloy rolled sheet obtained in Example 2 of the present invention.

[0032] Figure 3 This is the metallographic structure of the Mg-3Zn-0.2Y-0.5Ca-0.2Mn alloy sheet obtained in Example 2 of the present invention.

[0033] Figure 4 1 is the stress-strain curve of the magnesium alloy sheet obtained in Examples 1 and 2 of the present invention.

[0034] Figure 5 This is a bar graph showing the thermal conductivity of the magnesium alloy sheets obtained in Examples 1 and 2 of the present invention.

[0035] Figure 6 This is the macroscopic morphology of the Mg-3Zn-0.2Y-0.5Ca-0.2Mn alloy extruded plate in Comparative Example 1 of the present invention.

[0036] Figure 7 This is the macroscopic morphology of the Mg-3Zn-0.2Y-0.5Ca-0.2Mn alloy rolled plate in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0037] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0038] In the following examples, unless otherwise specified, raw materials or processing techniques are conventional commercially available raw materials or conventional processing techniques in the art.

[0039] Example 1

[0040] The high thermal conductivity magnesium alloy sheet has the following elemental components: zinc: 3.0wt.%, yttrium: 0.2wt.%, manganese: 0.2wt.%, and the remainder is magnesium and inevitable impurities.

[0041] (1) Casting

[0042] First, the pure magnesium ingot is polished clean, placed in a crucible, and heated to 720°C. After the magnesium ingot is completely melted, magnesium-calcium master alloy, pure zinc particles, magnesium-yttrium master alloy, and magnesium-manganese master alloy are added and allowed to stand for 20 minutes; then stirred for 2 minutes to ensure that the alloy solution is fully mixed. After the melt has been allowed to stand for 20 minutes, a refining agent is added and stirred for 2 minutes to remove the surface residue obtained after refining; then the melt is kept at 700°C for 30 minutes to remove the surface slag and oxide layer, and then poured into a metal mold to obtain a cast Mg-3Zn-0.2Y-0.2Mn alloy;

[0043] The refining agent is composed of covering agent RJ-2 and CaF2, and the mass ratio of covering agent RJ-2 to CaF2 is 19:1; the amount of refining agent added is 8 grams of refining agent corresponding to each kilogram of alloy;

[0044] The whole process is always introduced with a flowing mixed gas, wherein the mixed gas is composed of 99 vol.% CO2 and 1 vol.% SF6;

[0045] The weight percentage of calcium in the magnesium-calcium master alloy described in step 1 is 20%, the weight percentage of yttrium in the magnesium-yttrium master alloy is 30%, and the weight percentage of manganese in the magnesium-manganese master alloy is 20%;

[0046] The mold used for casting in step 1 is a steel mold, and the mold is preheated at 200° C. before casting.

[0047] (2) Homogenization

[0048] First, the obtained Mg-3Zn-0.2Y-0.2Mn alloy ingot is processed to the extrusion size; the homogenization process is: 320℃6h+430℃14h+520℃4h (i.e., first heat treatment at 320℃ for 6h, then heat treatment at 430℃ for 14h, and finally heat treatment at 520℃ for 4h), and then put it into water for quenching treatment; argon is used as the protective gas during the heat treatment process;

[0049] (3) Hot extrusion

[0050] First, the homogenized Mg-3Zn-0.2Y-0.2Mn alloy was preheated at 300°C for 30 minutes, and the hot extrusion die with an extrusion ratio of 25:1 was preheated to 350°C and kept warm, and then extruded at an extrusion speed of 5mm / s. Then, a magnesium alloy sheet with a width of 150mm and a thickness of 9mm was obtained.

[0051] (4) Rolling

[0052] First, the extruded Mg-3Zn-0.2Y-0.2Mn alloy plate was rolled, and the parameters in the multi-pass rolling process are shown in Table 1 below.

[0053] Before each rolling pass, the magnesium alloy sheet is kept warm in a heating furnace at 320°C. The holding time varies with the thickness of the sheet: 10-5 mm, 30 min; 5-2 mm, 20 min; <2 mm, 10 min.

[0054] The diameter of the roller used is 400mm, and the rolling speed is 20 revolutions per minute; the roller used has a built-in resistance heating rod and a temperature sensor; the roller temperature is controlled at about 200°C.

[0055] (5) Annealing

[0056] The rolled Mg-3Zn-0.2Y-0.2Mn alloy sheet was annealed.

[0057] The annealing temperature is 300°C and the time is 10 minutes. After the time is up, the magnesium alloy sheet is taken out and placed in the air to cool naturally.

[0058] The annealing process in step (5) is carried out in a vacuum heat treatment furnace under a pure argon protective atmosphere to ensure that the magnesium alloy ingot is not in contact with the outside air.

[0059] Table 1 Parameter changes during multi-pass rolling

[0060] Rolling pass Temperature(℃) Plate thickness change (mm) Compression amount (%) 1 320 9→8.28 8 2 320 8.28→6.86 15 3 320 6.86→5.49 20 4 320 5.49→3.84 30 5 320 3.84→2.69 30 6 320 2.69→1.88 30 7 320 1.88→1.13 40 8 320 1.13→0.68 40

[0061] The yield strength of the Mg-3Zn-0.2Y-0.2Mn alloy sheet obtained in this embodiment is 198.5MPa, the tensile strength is 294.7MPa, and the elongation is 13%. The stress-strain curve is shown in FIG. Figure 4 The thermal diffusion coefficient of the Mg-3Zn-0.2Y-0.2Mn alloy sheet obtained in this embodiment is 75.3m 2 / s, thermal conductivity is 134W / (m·K), as shown in Figure 5 As shown in the bar chart No. 1.

[0062] Example 2

[0063] The high thermal conductivity magnesium alloy sheet of this embodiment has the following elemental components in mass content: zinc: 3wt.%, yttrium: 0.2wt.%, calcium: 0.5wt.%, manganese: 0.2wt.%; the remainder is magnesium and unavoidable impurities.

[0064] (1) Casting

[0065] First, the pure magnesium ingot is polished clean, placed in a crucible, and heated to 720°C. After the magnesium ingot is completely melted, magnesium-calcium master alloy, pure zinc particles, magnesium-yttrium master alloy, and magnesium-manganese master alloy are added and allowed to stand for 20 minutes; then stirred for 2 minutes to ensure that the alloy solution is fully mixed. After the melt has been allowed to stand for 20 minutes, a refining agent is added and stirred for 2 minutes to remove the surface residue obtained after refining; then the melt is kept at 700°C for 30 minutes to remove the surface slag and oxide layer, and then poured into a metal mold to obtain a cast Mg-3Zn-0.2Y-0.5Ca-0.2Mn alloy;

[0066] The refining agent used is composed of covering agent RJ-2 and CaF2, and the mass ratio of covering agent RJ-2 to CaF2 is 19:1; the amount of refining agent added is 8 grams of refining agent corresponding to each kilogram of alloy;

[0067] The whole casting process is always fed with a flowing mixed gas, which is composed of 99 vol.% CO2 and 1 vol.% SF6;

[0068] The weight percentage of calcium in the magnesium-calcium master alloy is 20%, the weight percentage of yttrium in the magnesium-yttrium master alloy is 30%, and the weight percentage of manganese in the magnesium-manganese master alloy is 20%;

[0069] The mold used for casting is a steel mold, and the mold is preheated at 200°C before casting.

[0070] (2) Homogenization

[0071] First, the obtained Mg-3Zn-0.2Y-0.5Ca-0.2Mn alloy ingot was processed to the extrusion size; the homogenization process was: 320℃6h+430℃14h+520℃4h, after which it was put into water for quenching treatment; argon was used as the protective gas during the heat treatment;

[0072] (3) Hot extrusion

[0073] First, the homogenized Mg-3Zn-0.2Y-0.5Ca-0.2Mn alloy was preheated at 300°C for 30 minutes, and the hot extrusion die with an extrusion ratio of 25:1 was preheated to 350°C and kept warm, and then extruded at an extrusion speed of 5mm / s. Then, a magnesium alloy sheet with a width of 150mm and a thickness of 9mm was obtained.

[0074] (4) Rolling

[0075] First, the extruded Mg-3Zn-0.2Y-0.5Ca-0.2Mn alloy plate was rolled, and the parameters in the multi-pass rolling process are shown in Table 2 below.

[0076] Before each rolling pass, the magnesium alloy sheet is kept warm in a heating furnace at 320°C. The holding time varies with the thickness of the sheet: 10-5 mm, 30 min; 5-2 mm, 20 min; <2 mm, 10 min.

[0077] The diameter of the roller used in this step is 400 mm, and the rolling speed is 20 rpm; the roller used has a built-in resistance heating rod and a temperature sensor; the roller temperature is controlled at about 200°C.

[0078] (5) Annealing

[0079] The rolled Mg-3Zn-0.2Y-0.5Ca-0.2Mn alloy sheet was annealed.

[0080] The annealing temperature is 300°C and the time is 10 minutes. After the time is up, the magnesium alloy sheet is taken out and placed in the air to cool naturally.

[0081] The annealing process in step (5) is carried out in a vacuum heat treatment furnace under a pure argon protective atmosphere to ensure that the magnesium alloy ingot is not in contact with the outside air.

[0082] Table 2 Parameter changes during multi-pass rolling

[0083]

[0084]

[0085] The yield strength of the Mg-3Zn-0.2Y-0.5Ca-0.2Mn alloy sheet obtained in this embodiment is 240MPa, the tensile strength is 327MPa, and the elongation is 13%. The stress-strain curve is shown in FIG. Figure 4 The thermal diffusion coefficient of the Mg-3Zn-0.2Y-0.5Ca-0.2Mn alloy sheet obtained in this embodiment is 77.2m 2 / s, thermal conductivity is 137.5W / (m·K), as shown in Figure 5 As shown in the bar chart No. 2.

[0086] In addition, the mechanical properties of the alloy sheets obtained in Example 1 and Example 2 (test method refers to GB / T228.1-2021) are shown in Table 3 below.

[0087] Table 3

[0088] Yield strength(MPa) Tensile strength(MPa) Elongation(%) Example 1 198.08 294.78 13.14 Example 2 242.31 328.3 12.96

[0089] Comparative Example 1

[0090] Compared with Example 2, most of the above are the same, except that the homogenization heat treatment in step (2) is not performed. The macroscopic morphology of the extruded plate of Comparative Example 1 is as follows: Figure 6 As shown, it can be seen that the extruded plate is covered with large-sized through cracks, which is mainly due to the large second phase and component segregation in the cast structure, which are not conducive to high-temperature extrusion deformation of the alloy.

[0091] Comparative Example 2

[0092] Compared with Example 2, most of the above are the same, except that the rolling temperature during the rolling process is adjusted to 400°C. The macroscopic morphology of the rolled plate of Comparative Example 2 is as follows: Figure 7 As shown in the figure, it can be seen that after multiple rolling passes, the center of the plate is covered with microcracks and accompanied by serious edge cracks. This may be due to the fact that the grains of the rolled plate are large under high temperature conditions, which is not conducive to plastic deformation. In addition, the incoordination of stress and strain borne by various parts of the plate during the rolling process can easily lead to its plastic rheological instability.

[0093] Figure 1 This is the macroscopic morphology of the Mg-3Zn-0.2Y-0.5Ca-0.2Mn alloy extruded plate in Example 2. It can be seen that the surface of the plate is smooth and bright. Figure 2 This is the macroscopic morphology of the Mg-3Zn-0.2Y-0.5Ca-0.2Mn alloy rolled sheet obtained in Example 2. It can be seen that its surface is smooth and bright, without any cracks, and its thickness is only 0.75 mm. Figure 3 The metallographic structure of the Mg-3Zn-0.2Y-0.5Ca-0.2Mn alloy sheet obtained in Example 2 shows that the average grain size is 16 mm and twins exist. Figure 4 The tensile stress-strain curves of Examples 1 and 2 are shown in FIG. Figure 5 The thermal conductivity of Examples 1 and 2. Comparing Examples 1 and 2, it can be seen that the addition of Ca element can improve the strength and enhance the thermal conductivity of the magnesium alloy sheet. Although Comparative Examples 1 and 2 have the same alloy composition as Example 2, only the heat treatment and rolling processes are different, but their forming capabilities are limited and they fail to successfully prepare magnesium alloy sheets. It can also be confirmed that the alloying elements selected in this application and their casting, heat treatment, extrusion and rolling deformation processes are carefully designed, and they have a direct impact on the forming properties, mechanics and thermal conductivity of the high thermal conductivity magnesium alloy sheet.

[0094] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A high thermal conductivity magnesium alloy sheet, characterized in that: It is composed of the following elements in weight percentage: Zn 1.0% to 5.0%, Y 0% to 0.8%, Ca 0% to 0.7%, Mn 0.1% to 0.5%, and the rest are Mg and inevitable impurities.

2. The high thermal conductivity magnesium alloy sheet according to claim 1, characterized in that: The content of Y is not 0; And / or, the Ca content is not zero.

3. The high thermal conductivity magnesium alloy sheet according to claim 1, characterized in that: The content of Zn is 3%, the content of Y is 0.2%, the content of Ca is 0.5%, and the content of Mn is 0.2%.

4. A method for preparing a high thermal conductivity magnesium alloy sheet according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) heating and melting raw materials providing Zn, Y, Ca, Mn and Mg to obtain a mixed solution, keeping the solution at the temperature and allowing it to stand, cooling the solution to remove the slag and oxide layer on the surface, and then casting the solution to obtain a magnesium alloy ingot; (2) subjecting the obtained magnesium alloy ingot to homogenization heat treatment, and then quenching to obtain a homogenized ingot; (3) preheating the homogenized ingot and then isothermally extruding it to obtain a magnesium alloy sheet; (4) The magnesium alloy sheet is hot rolled and annealed to obtain a magnesium alloy thin plate, which is the product.

5. The method for preparing a high thermal conductivity magnesium alloy sheet according to claim 4, characterized in that: The raw materials for providing Zn, Y, Ca, Mn and Mg include pure magnesium, magnesium-calcium master alloy, pure zinc particles, magnesium-yttrium master alloy and magnesium-manganese master alloy.

6. The method for preparing a high thermal conductivity magnesium alloy sheet according to claim 4, characterized in that: Step (1) During the preparation of the magnesium alloy ingot, a flowing mixed gas is introduced for anti-oxidation protection, wherein the mixed gas consists of 99 vol. % CO2 and 1 vol. % SF6.

7. The method for preparing a high thermal conductivity magnesium alloy sheet according to claim 4, characterized in that: In step (2), the process conditions of the homogenization heat treatment are: first heat treatment at 320°C for 6 hours, then heat treatment at 430°C for 14 hours, and finally heating to 520°C for 4 hours; The homogenization heat treatment process is carried out in a vacuum heat treatment furnace under a pure argon protective atmosphere.

8. The method for preparing a high thermal conductivity magnesium alloy sheet according to claim 4, characterized in that: In step (3), the preheating temperature is 250°C to 400°C; The process conditions of isothermal extrusion are: extrusion ratio of 10-25:1, extrusion speed of 0.01 mm·s -1 ~25mm·s -1 , the extrusion temperature is 200℃~350℃.

9. The method for preparing a high thermal conductivity magnesium alloy sheet according to claim 4, characterized in that: In step (4), the magnesium alloy is subjected to multiple hot rolling passes, wherein the reduction in the first rolling pass is controlled at 5% to 10%, the reduction in the intermediate rolling passes is controlled at 10% to 30%, and the reduction in the final rolling pass is controlled at 10% to 40%; Before each rolling pass, the magnesium alloy plate is kept at 300-350°C, and the holding time varies with the thickness of the plate. When the thickness of the magnesium alloy plate is 5-10mm, the holding time is 30min; when the thickness of the magnesium alloy plate is 2-5mm, the holding time is 20min; when the thickness of the magnesium alloy plate is less than 2mm, the holding time is 10min.

10. The method for preparing a high thermal conductivity magnesium alloy sheet according to claim 4, characterized in that: In step (4), the annealing temperature is 200°C to 350°C, and the annealing time is 10 minutes to 2 hours.

Citation Information

Patent Citations

  • Preparation method of high-strength and high-thermal-conductivity magnesium alloy

    CN113652565A

Cited By

  • Magnesium alloy and preparation method therefor, structural member, and electronic device

    WO2026194635A1